The ‘Nasyon': a critical exploration of the ‘Nasyon's' persisting dissociation from political power in Mauritius - Dewoo, Moshumee Teena (African Studies, 2023)
The ‘Nasyon', persons of (imagined, claimed, and proclaimed unmixed) black African ancestry in Mauritius, have always stood at the lowest rungs of the Mauritian socio-political hierarchy, persistently dissociated from political power therein. In this thesis, I set out to uncover and explore the reasons for this through the prism of historical ethnography and from the following question: What are the modes of action (x) that give rise to the ‘Nasyon's' persisting dissociation from political power in Mauritius (y)? From and through this prism, I find the ‘Nasyon' to have been fixed as permanently incomplete humans, if human at all, and their incompleteness to have been institutionalised toward keeping them at the margins of the country as non-citizens thereof. Naturally, they could not access or should not be allowed access to political power. To get to political power, they would need to be complete or be made so, as per the claims and requests of political observers and activists on the matter of the marginalisation of persons of black African ancestry. This is the quest for completeness. But this quest is problematic because completeness is unreal, and incompleteness is the normal order of things in the socio-political world. I take from the works of Amos Tutuola and Francis Nyamnjoh to explain this, putting incompleteness forward as a more wholesome lens from and through which to read the case of the ‘Nasyon's' persisting dissociation from political power in Mauritius: the ‘Nasyon' are incomplete humans, but this is not a problem to be solved.